2016
DOI: 10.18865/ed.26.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Campaign for the Early Detection of Growth Disorders in Public School Children in North Lebanon

Abstract: <p><strong>Objectives: </strong>To detect and screen growth anomaly among children in North Lebanon, raise awareness on the importance of regular height check, and establish recommendations for the authorities. <strong></strong></p><p><strong>Design: </strong>18-month campaign. <strong></strong></p><p><strong>Setting: </strong>230 public schools in North Lebanon. </p><p><strong>Participants: </strong&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…However, the extent of their knowledge is unclear, as is how they gathered the knowledge they do have and how they approach short stature, including the timing for seeking a referral for their child to pediatric and endocrine specialty clinics for evaluation. In North Lebanon, a study conducted by Hayek et al [8] focused on an awareness campaign for the early recognition of growth disorders in public schoolchildren. The researchers concluded that screening campaigns indicate the necessity of more awareness about the significance of early detection of growth disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent of their knowledge is unclear, as is how they gathered the knowledge they do have and how they approach short stature, including the timing for seeking a referral for their child to pediatric and endocrine specialty clinics for evaluation. In North Lebanon, a study conducted by Hayek et al [8] focused on an awareness campaign for the early recognition of growth disorders in public schoolchildren. The researchers concluded that screening campaigns indicate the necessity of more awareness about the significance of early detection of growth disorders.…”
Section: Introductionmentioning
confidence: 99%